Superhydrophobic graphene-based materials with self-cleaning and anticorrosion performance: An appraisal of neoteric advancement and future perspectives (2020)
Lotus like materials having superhydrophobicity is attaining greater demand due to the possibility of molding them into different high end applications. The major issue related to self-cleaning superhydrophobic surfaces is their restricted mechanical properties. The development of nanotechnology has brought many advantages in the fabrication and properties of superhydrophobic surfaces and thus it enhanced the demand of superhydrophobic surfaces. Many scientific groups have studied and reported about the superhydrophobicity exhibited by graphene and its analogous derivatives. The fabrication of the devices having properties ranging from antisticking and self-cleaning to anti-corrosion and low friction is made possible by the incorporation of this wonderful two-dimensional material. This review focuses on the preparation and properties of graphene based superhydrophobic coating materials with special mention to the wide range of applications rendered by them.